Genetic variability, heritability and genetic advance in cucumber (Cucumis sativus L.) - Bartaula, Sampurna; Adhikari, Anil; Panthi, Urbashi; Karki, Prabesh; Timalsena, Kiran (Journal of Agriculture and Natural Resources, 2019)
Genetic variability in a crop population is important for successful plant breeding. Eight cucumber (Cucumis sativus L.) genotypes namely Green Long, Simran, Bhaktapur Local, Saihni-2, Ninja-179, Garima, Farmer’s variety and wild genotype were evaluated at Lamahi Municipality, Dang district of Nepal to estimate the magnitude of their genetic variability and heritability. Analysis of variance revealed significant differences among genotypes for growth and yield traits. The estimates of genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were highest for weight of fruit whereas traits namely fruit length, fruit diameter and days to maturity had medium value for both GCV and PCV. Broad sense heritability estimates ranged from 0.74 for fruit diameter to 0.98 for days to germination. Fruit yield showed high significant positive correlation with fruit diameter (r= 0.649) and negative significant correlation (r= -0.538) with days to flowering. Traits namely weight per fruit, days of germination, no. of flower and days to flowering can be used effectively in selection process of crop improvement program as they had high GCV, PCV and heritability along with high genetic advance as percentage of mean.